C# 10 in a nutshell - Albahari, Joseph (O'Reilly Media, Inc., 2022)
When you have questions about C# 10.0 or .NET 6, this bestselling guide has the answers you need. C# is a language of unusual flexibility and breadth, but with its continual growth, there's so much more to learn. In the tradition of O'Reilly's Nutshell guides, this thoroughly updated edition is simply the best one-volume reference to the C# language available today. Organized around concepts and use cases, this comprehensive and complete reference provides intermediate and advanced programmers with a concise map of C# and .NET that also plumbs significant depths.
Online resource; Title from title page (viewed February 15, 2022)
Keywords: C# (Computer program language); C# (Langage de programmation)